Disruptive Potential of IoT Medical Devices on Medical Diagnostics Market - Julia KUDLA (Communications of International Proceedings, 2021)
For years there has been number of challenges and barriers blocking the implementation of the IoT system in eHealth sector. Due to the new premises discussed in the paper, the prospects on widespread implementation of IoT medical devices improve. The objective of this paper is to discuss the potential impact of IoT medical devices to disrupt the medical diagnostics market. The paper is intended to be a review of the field, indicating a new context revealing impending changes. Its results reveal that IoT innovations in medical diagnostics market are more likely to be widespread since the pandemic due to a progressing digitization, growing demand for remote patient monitoring and legal facilitations. Also, expected implementation of fifth-generation wireless network technology and developments of biosensors, foreshadow a new era of eHealth.
Keywords: Disruptive ICT; Iot; Ioht; Medical Diagnosis.